Randomized trial of care management to improve Parkinson disease care quality. (16th April 2019) - Connor, Karen I.; Cheng, Eric M.; Barry, Frances; Siebens, Hilary C.; Lee, Martin L.; Ganz, David A.; Mittman, Brian S.; Connor, Megan K.; Edwards, Lisa K.; McGowan, Michael G.; Vickrey, Barbara G.
Abstract : Objective: To test effects on care quality of Chronic Care Model-based Parkinson disease (PD) management. Methods: This 2-group stratified randomized trial involved 328 veterans with PD in southwestern United States. Guided care management, led by PD nurses, was compared to usual care. Primary outcomes were adherence to 18 PD care quality indicators. Secondary outcomes were patient-centered outcome measures. Data sources were telephone survey and electronic medical record (EMR). Outcomes were analyzed as intent-to-treat comparing initial and final survey and repeated-measures mixed-effects models. Results: Average age was 71 years; 97% of participants were male. Mean proportion of participants receiving recommended PD care indicators was significantly higher for the intervention than for usual care (0.77 vs 0.58) (mean difference 0.19, 95% confidence interval [CI] 0.16, 0.22). Of 8 secondary outcomes, the only significant difference of the changes over time was in the positive Patient Health Questionnaire–2 depression screen for intervention minus usual care (−11.52 [95% CI −20.42, −2.62]). Conclusion: A nurse-led chronic care management intervention, Care Coordination for Health Promotion and Activities in Parkinson's Disease (CHAPS), substantially increased adherence to PD quality of care indicators among veterans with PD, as documented in the EMR. Of 8 secondary outcomes assessed, a screening measure for depressive symptomatology was the only measure that was better in the intervention compared to usual care. More telephone calls in CHAPS were the only utilization difference over usual care. While CHAPS appears promising for improving PD care, additional iterative research is needed to refine the CHAPS model in routine clinical care so that it measurably improves patient-centered outcomes (NCT01532986). Classification of evidence: This study provides Class I evidence that for patients with PD, CHAPS increased adherence to PD quality of care indicators.